1969
DOI: 10.1139/m69-054
|View full text |Cite
|
Sign up to set email alerts
|

Astringency in fruits. I. Microbial degradation of catechin

Abstract: Four molds (Aspergillus fumigatus, A. terreus, A. niger, Penicillium species) and a Streptomyces species capable of degrading catechin were isolated from soil by enrichment techniques. These organisms and Aspergillus flavus (dicat), isolated from a dicatechin medium, were compared for their ability to degrade catechin. The studies indicated that A. flavus (dicat) was the most active of the organisms tested. The degradation of catechin by A. flavus (dicat) was optimal at pH 5.0 and 0.3% catechin. Phloroglucinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Tannic acid (TA) (penta‐ m ‐digalloyl‐glucose) is a natural polyphenolic compound found in some galls of Quercus species (oaks, Quercus infectoria , etc), Rhus species (sumacs, R. coriaria, R. glabra, Rhus thypia ), beverages (red wine, tea, coffee), fruits, and vegetables. This hydrolyzable tannin is produced on young oak/sumac twigs by a gall wasp ( Andricus gallate tinctorial ) or other insects and yields gallic acid and glucose . It is used for treating burn injuries, healing wounds, cold sores, bleeding, chronic diarrhea, and so forth and as a flavouring agent .…”
Section: Introductionmentioning
confidence: 99%
“…Tannic acid (TA) (penta‐ m ‐digalloyl‐glucose) is a natural polyphenolic compound found in some galls of Quercus species (oaks, Quercus infectoria , etc), Rhus species (sumacs, R. coriaria, R. glabra, Rhus thypia ), beverages (red wine, tea, coffee), fruits, and vegetables. This hydrolyzable tannin is produced on young oak/sumac twigs by a gall wasp ( Andricus gallate tinctorial ) or other insects and yields gallic acid and glucose . It is used for treating burn injuries, healing wounds, cold sores, bleeding, chronic diarrhea, and so forth and as a flavouring agent .…”
Section: Introductionmentioning
confidence: 99%
“…Production of tannase increased with the concentration of tannic acid. Chandra et al (1973) reported that the degradation of wood apple tannin by A. niger and Penicillium sp. occurred only in glucose medium.…”
Section: Culture Conditions Favouring Degradation Of Tanninsmentioning
confidence: 99%